Legal Issues in the Use of Student Test Scores and Value-added Models (VAM) to Determine Educational Quality - Diana Pullin (Arizona State University, 2013)
A growing number of states and local schools across the country have adopted educator evaluation and accountability programs based on the use of student test scores and value-added models (VAM).  A wide array of potential legal issues could arise from the implementation of these programs. This article uses legal analysis and social science evidence to discuss potential legal challenges by educators to the use of VAM that should be considered by public policy makers.  It also discusses potential ways VAM might be used as evidence in support of legal claims by students concerning access to educational opportunity.